The role of public-private partnerships in attracting investment projects in the transport sector - Mardievna, Shodieva Gulnora; Boltaevna, Shakirova Farogat (The journal of contemporary issues in business and government, 2021)
The article examines foreign mechanisms of public-private partnership as the most effective form of public-private partnership, the possibility of effective organization of public-private partnership in the transport sector and the implementation of investment projects to ensure sustainable economic growth, draws conclusions, proposals and recommendations. out